IDENTIFIKASI DAERAH JELAJAH SIMPAI (Presbytis melalophos) MENGGUNAKAN APLIKASI SISTEM INFORMASI GEOGRAFIS DI CAMP GRANIT TAMAN NASIONAL BUKIT TIGA PULUH - Rostika, Lina; Yoza, Defri; Oktorini, Yossi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2021)
Simpai (Presbytis melalophos)Â  or Sumatran surili is one of the primate species that has an important role for nature in the smooth process of natural forest succession. Simpai (Presbytis melalophos) is one of the endemic monkeys on the island of Sumatra from the family Cercopithecidae which is a rare and threatened primate based on the Regulation of the Minister of Environment and Forestry of the Republic of Indonesia Number P.20/MENLHK/SETJEN /KUM.1/62018. Camp Granite is one of the hoop habitat locations in Bukit Tiga Puluh National Park. However, until now there has been no information reporting research on hoops in the area. This study aims to find out information about the roaming area of the Simpai group (Presbytis melalophos) at Camp Granite Bukit Tiga Puluh National Park. The data collection in this study used a concentrated observation method with direct and hidden observations so as not to interfere with hoop activities. The data were analyzed using a geographic information system, namely the ArcGis 10.3 application. Based on the data results, the hoop group in the Camp Granite area has a roaming area of 3.66 ha. The range of hoops in thearea Camp Graniteis at coordinates S 00Âº 49' 42,240â€, E 102Âº 31' 37,380â€- S 00Âº 49' 53,040â€, E 102Âº 31' 40,440â€ and S 00Âº 49' 46,620â€, E 102Âº 31' 35,160â€-S 00Âº 49' 50,400â€, E 102Âº 31' 42,300â€Keywords: Simpai (Presbytis melalophos), Roaming Area, Camp Granit.